DOI: 10.11606/t.64.2009.tde-03122009-094223
|View full text |Cite
|
Sign up to set email alerts
|

Silício em plantas de feijão e arroz: absorção, transporte, redistribuição e tolerância ao cádmio

Abstract: A todos meus queridos irmãos... e Ao Jackson, Pelo apoio, carinho e dedicação. OFEREÇO v AGRADECIMENTOSA Deus por ter me concedido a dádiva de viver essa parte da minha história de vida em Piracicaba, local onde Ele me encheu de bênçãos.Ao Centro de Energia Nuclear na Agricultura (CENA) da Universidade de São Paulo, pela estrutura oferecida para o desenvolvimento de meus trabalhos.Ao Prof. Dr. Cassio Hamilton Abreu Junior, meu orientador de tese, que sempre com muita paciência trabalhou junto a mim e enfrentou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
8

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 86 publications
(335 reference statements)
2
6
0
8
Order By: Relevance
“…These results highlight the different Si response between Fabaceae and Poaceae. They also corroborate with those obtained using a Si nutrient solution, whereby rice and wheat (accumulative) showed a low absorption of Si in the initial phase, which gradually increased over time, while bean and soy (non-accumulative) only absorbed high levels of Si in the initial week (Oliveira 2009).…”
Section: Discussionsupporting
confidence: 87%
“…These results highlight the different Si response between Fabaceae and Poaceae. They also corroborate with those obtained using a Si nutrient solution, whereby rice and wheat (accumulative) showed a low absorption of Si in the initial phase, which gradually increased over time, while bean and soy (non-accumulative) only absorbed high levels of Si in the initial week (Oliveira 2009).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the study by Pereira Júnior, Rezende 27 on the response of soybean to different doses of silicon found a positive response for plant height and number of pods per plant with increasing doses. Conversely, Oliveira 28 reported that the application of silicon in the nutrients solution to soybean plants did not have a significant effect on dry matter production 30, 45 and 60 days after emergency. Silicon absorption by soybean plants is highly variable and may in some cases do not show effects on the analyzed variables, because such effects may be associated to more internal features of the plants, for example to the growth of the cell wall or to the resistance to pests and diseases and to biotic and abiotic stress factors.…”
Section: Discussionmentioning
confidence: 94%
“…Também está envolvido na tolerância a estresses abióticos, como o salino, tornando as células mais tolerantes (EPSTEIN, 1999). Esses fatores fizeram com que, no Brasil, o silício passasse a fazer parte da lista de micronutrientes, embora as pesquisas ainda não tenham demonstrado a essencialidade deste elemento (OLIVEIRA, 2009). …”
Section: Introductionunclassified